Rwanga Movement and Cultural Critical Speech - Mohammed Ahmed Hasan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
Cultural Criticism in Literature was of a reaction toward Structuralism and Semiology, which would see literature as a linguistic phenomenon. In other words, literature used to be an artistic, esthetic and poetic phenomenon. But, cultural criticism emerges and releases literature from that framework and becomes a new method for studying that cultural structure which has created that literature, simultaneously, studying literature from its cultural, social, historical and political context. In our viewpoint, Rwanga Movement was more of a cultural phenomenon than a literary one such as a piece of text. This research (Rwanga Movement and Cultural Critical Speech) consists of two chapters. The first chapter is a literary chapter containing three sections. The first section discusses terminology related to cultural criticism. The second section is dedicated to cultural criticism which replaces literary criticism, and how wider the area cultural criticism works in than that of literary criticism. The third section discusses the cultural speech of Rwanga Movement for which we have worked on the Movement’s manifest. The second chapter is a applied work containing two parts. The first part discusses the role of Rwanga movement on how it works on the structure of the making of literary text. The second part discusses the aging of Kurdish literature and the role of Rwanga movement in its revival as a cultural phenomenon. The result of our research is discussed in some points. The Harvard system has been used for the list of the references.